The Babylonian entitlement narûs (kudurrus) a study in their form and function - Slanski, Kathryn E. (Boston, Mass. American Schools of Oriental Research, 2003)
Rough chronology for Mesopotamian historical periods -- The cuneiform languages of Mesopotamia -- Area measures in field descriptions -- Introduction -- Designation and setting -- The inscriptions : subject and structure -- Form and function -- Formal definition for the Babylonian entitlement narûs -- Debatable members of the corpus -- The place of the Babylonian entitlement narûs in Mesopotamian culture -- Conclusion -- Appendices
Mit babylon. Textausz. in lat. Schr
Zugl.: Cambridge, Mass., Harvard Univ., Diss., 1997
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Relief (Sculpture), Assyro-Babylonian; Stele (Archaeology) -- Iraq -- Babylonia; Boundary stones -- Iraq -- Babylonia; Stele Archaeology -- Iraq -- Babylonia; Boundary stones -- Iraq -- Babylonia; Relief Sculpture, Assyro-Babylonian; Cuneiform inscriptions, Akkadian; Hochschulschrift